HOW AUTONOMOUS CARS WILL INFLUENCE THE CAR INSURANCE MARKET - Pisano, Simone (2020)
The car market has always been considered as a mature market, immune from the influence of the major external factors. However, nowadays, it has been going through a complete transformation caused by the introduction of ever more advanced self-driving technologies that will change the relations with the customers and how they will approach to the transportation market.As a result, the new technology will not influence only the car manufacturers and the customers but will, for the first time, affect a pool of new stakeholders such as technological companies, software houses other than regulators and consequently, in an even larger scale, the insurance sector.Insurance companies will see their business evolving at a faster pace than ever with lower profits in their old core business and new competitors entering their influence area. An increased awareness of this evolution will be fundamental for the players of this market that will have to understand how to face the coming revolution. The new challenge will be both on taking advantage of the new opportunities offered and, staying alert on keeping the profitability of the old businesses. To do so, the right expertise in the new technologies has to be boosted making possible the transition to the new technological paradigms.This paper aims to analyse every aspect of this evolution to predict the possible outcomes and to provide useful advices to the insurance companies on how to stay successfully in control of their business and how to expand their influence to the new boundaries of technological evolution. This research aims to gather a general knowledge on the implications of new technologies applied to cars and in-depth insights on the consequences of these new technologies for the insurance market.